Madagascar : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper analyzes recent economic developments and policies in Madagascar. Real GDP growth in 2001 was 6 percent, continuing the trend of sustained increase in per capita real GDP that began during the period 1997-2000. The secondary and tertiary sectors were the main sources of growth. The value added of the secondary sector, which accounts for only 13.3 percent of output, increased by 7.6 percent in 2001, following an annual average increase of 5 percent in 1997-2000.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet